2020
DOI: 10.1177/0042085920902244
|View full text |Cite
|
Sign up to set email alerts
|

“Educate Your Heart Before Your Mind”: The Counter-Narratives of One African American Female Teacher’s Asset-, Equity- and Justice-Oriented Pedagogy in One Urban School

Abstract: This article narrates one African American female teacher’s asset-, equity-, and justice-oriented pedagogy with foci on culturally responsive pedagogy and authentic caring in teaching in an urban school from the joint perspectives of community cultural wealth, funds of knowledge, and funds of identity. Drawing upon humanizing counter-narrative research methodologies, this article foregrounds traditionally oppressed groups’ repressed voices concerning culturally responsive pedagogy and authentic caring for impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…FoI scholars have developed a fully elaborated, substantial, and theoretically grounded approach that has the potential to make a substantial contribution to countering deficit thinking and achieving schooling that is culturally inclusive within our superdiverse societies. It remains productive in generating empirical research (e.g., Oikonomidoy & Karam, 2020; Villacañas de Castro, 2020; Zhang-Yu et al, 2020; Zhu, 2020). We also note that outside the “niche” of the FoI and FoK conceptual framework, several studies addressed questions related to making education more relevant for students through making learning more personally meaningful (Chaffey, 2018; Hedges, 2018; Silseth, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…FoI scholars have developed a fully elaborated, substantial, and theoretically grounded approach that has the potential to make a substantial contribution to countering deficit thinking and achieving schooling that is culturally inclusive within our superdiverse societies. It remains productive in generating empirical research (e.g., Oikonomidoy & Karam, 2020; Villacañas de Castro, 2020; Zhang-Yu et al, 2020; Zhu, 2020). We also note that outside the “niche” of the FoI and FoK conceptual framework, several studies addressed questions related to making education more relevant for students through making learning more personally meaningful (Chaffey, 2018; Hedges, 2018; Silseth, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Today's society, marked by the heterogeneity of its citizens, requires concrete actions to achieve a truly inclusive education that offers equal opportunities for all students regardless of their ethnic background, socio-economic class, or gender [2,3]. It is relevant to note that inclusive education has become an indispensable principle for dealing with students' diversity.…”
Section: Discussionmentioning
confidence: 99%
“…From this vision, equity requires an unequal distribution of resources in the hope that sustained equity will temporarily favor and promote more equal educational opportunities for students, in which all reach the maximum possible development of their individual and social, intellectual, cultural and emotional capacities. Students should receive a quality education adapted to their needs, thus making equity and quality the two sides of the same coin [3]. This premise would imply that differences between people would not be a risk factor for discrimination, exclusion, or social, labor or educational disadvantage, but rather an opportunity to improve them [4] and to meet their needs.…”
Section: Introductionmentioning
confidence: 99%
“…Racial identity is defined as the significance and qualitative meaning that individuals attribute to their membership within a racial group (Livingston et al, 2020). Regarding teachers' black identity, in the narrative of a black teacher in a southwestern U.S. urban middle school by Zhu (2020), the teacher improved her students' academic performance by confirming the funds of their identities -she brought her students' community cultural wealth, such as rap, police brutality, immigration, and legal issues, into her classroom. In examining the relationship between racial identity and classroom discourse, Zhu (2020) suggested that this black teacher's story could inspire more urban teachers to reflect on their professional identities and repertoires of instruction; for instance, this teacher's culturally responsive pedagogy might act as a powerful lens through which urban teachers could examine sociopolitical discourses contributing to the "achievement debt.…”
Section: Diversity In Classroom Discourse Portrayed In Teachers' Storiesmentioning
confidence: 99%
“…Ethnicity portrayed in teachers' stories Zhu (2020) showed how teachers build identity in minorities and a (multi) cultural context. If students have the same ethnicity as the teacher, teachers might try to emancipate students in the sense that if they managed, the students will manage as well (upwards social mobility); they focus on a caring STORIES OF TEACHERS' IDENTITY relationship and support minority topics in the lessons (e.g., social justice) and delimit themselves against neoliberal educational politics (Zhu, 2020).…”
Section: Parenting Experience Portrayed In Teachers' Storiesmentioning
confidence: 99%